Production, characterization, and biological activity of a chitin-like EPS produced by Mortierella alpina under submerged fermentation. (1st November 2020) - Goyzueta M., Luis Daniel; Noseda, Miguel D.; Bonatto, Sandro J.R.; de Freitas, Rilton Alves; de Carvalho, Júlio Cesar; Soccol, Carlos Ricardo
Highlights: A chitin-like exopolysaccharide produced by Mortierella alpina was characterized. The optimization process resulted in 50 % increment of production. The exopolysaccharide was homogeneous and had a molar mass of 4.9 × 10 5 g mol −1 . The polysaccharide showed an antioxidant and antitumoral effect. The formation of hydrogels suggested the potential use of this exopolysaccharide as a biomaterial. Abstract: The production of a chitin-like exopolysaccharide (EPS) was optimized through experimental design methods, evaluating the influence of urea, phosphate, and glucose. Under optimized conditions, up to 1.51 g/L was produced and its physicochemical characteristics were evaluated by chromatography, NMR, and FTIR spectroscopy, and rheological techniques. The results showed a homogeneous EPS (Mw 4.9 × 10 5 g mol −1 ) composed of chitin, linear polymer of β-(1→4)-linked N -acetyl-d -glucosamine residues. The acetylation degree as determined by 13 C CP-MAS NMR spectroscopy was over 90 %. The EPS biological activities, such as antioxidant effect and antitumor properties, were evaluated. To the best of our knowledge, this is the first study on the production of a new alternative of extracellular chitin-like polysaccharide with promising bioactive properties from the filamentous fungus M. alpina.